Numerical simulation of structural, electronic and optical properties of transition metal chalcogenides - Rugut, Elkana Kipkogei (My University, 2017)
Intensive study on structural, electronic and optical properties of bulk transition metal dichalcogenides and dipnictogenides (MX2; where M = V, Nb and X = S, Se, Te, P) was undertaken. A relative stability test was done to determine the most stable ground state conﬁguration via calculation of total ground state energy and volume which was ﬁtted to the third order Birch-Murnaghan equation of state to extract lattice parameters. Cohesive energies of the above mentioned MX2 compounds and their elemental solids were then computed from which formation energies were acquired based on their respective equations of reaction between reactants and product. Its signiﬁcance was to aid in determining if a material is energetically stable. Elastic constants were predicted from which mechanical properties i.e bulk, Young’s and shear moduli and consequently Poisson’s ratio were resolved by feeding the stiﬀness matrix onto online elastic tensor analysis tool which facilitated veriﬁcation of their mechanical stability based on the well-known Born stability conditions which varies from one crystal system to another, at a later stage phonon dispersion curves were plotted after performing phonon calculation based on phonopy code to verify if the materials of concern are dynamically stable. After a material had fulﬁlled all the above stability tests, its structural study was initiated using various functionals. Functional that described best the structural properties of each individual compound considered was then applied in exploring its electronic and optical properties whose motivation was to ﬁnd out the most stable phase as well as gauge if these materials could be used in various ﬁelds that suits their mechanical and optical properties. Furthermore, from carefully calculated optical spectra, plasma frequencies were analyzed which indicated the possibility of applying a material in plasmonic related ﬁelds. In addition to above, other factors to be considered when selecting a given electrode material that are crucial for optoelectronics are good chemical and thermal stabilities, high transparency and excellent conductivity.
A dissertation submitted to the Faculty of Science University of the Witwatersrand, in partial fulfilment of the requirements for the degree of master of science (MSc) School of physics, University of Witwatersrand, 2017.
Keywords: Transition metals; Chalcogenides; Transition metals--Electric properties; Transition metals--Optical properties; Chalcogenides--Electric properties